Stable carbon isotopes trace the effect of fossil fuels on fractions of particulate black carbon in a large urban lake in China. (15th September 2022) - Meng, Lize; Huang, Changchun; He, Yao; Shang, Nana; Yu, Heyu; Huang, Tao; Yang, Hao; Zhao, Kan
Abstract: Black carbon (BC), the highly recalcitrant aromatic carbonaceous from the incomplete combustion of fossil fuel and biomass, is an important carbon sink in carbon cycle. Char and soot, the main components of BC, have significantly different origin and physicochemical characteristics (particle sizes and resultant transportability). The limited understanding of char and soot sources leads to poor insight into the effect of BC on carbon cycle. Sources of char and soot were investigated in this study using stable carbon isotopes to study the effect of BC on the organic carbon pool in a lake, thereby improving the knowledge of lacustrine carbon cycling. The concentration of BC in Taihu Lake ranged from 0.0 to 0.7 mg·L −1 and accounted for 10.9 ± 4.7% of the particulate organic carbon. The spatial-mean δ 13 C values of BC, char, and soot were −23.2 ± 2.0‰, −23.5 ± 2.2‰, and −22.9 ± 1.6‰, respectively. The BC in water was primarily derived from fossil fuels (66.0 ± 9.3%), with liquid fossil fuel accounting for 48.2 ± 13.2% of the BC. The contribution of liquid fossil fuel to soot (49.3%) was much higher than that to char (36.1%); correspondingly, the contributions of biomass and coal to soot (29.2% and 21.5%) were lower than those to char (38.1% and 25.8%). The contribution of liquid fossil fuel combustion to organic carbon (OC), char, and soot gradually increased from 31.9% to 49.3%. Biomass and coal combustion primarily contributed to char (38.1% and 25.8%) and OC (37.5% and 30.6%). The source apportionment of BC, char, and soot revealed the influence of anthropogenically driven BC, char, and soot on the lake and, by extension, to the global carbon cycle. Graphical abstract: Image 1 Highlights: Char and soot equally contribute to BC with a mean char/soot ratio of 1.2 ± 0.7. The contribution of fossil fuels to BC in Taihu Lake is 66.0 ± 9.3%. Soot is mainly derived from liquid fossil fuels combustion, and char is mainly derived from biomass burning.